Colon Directed Drug Transport by Way of AZO Prodrugs - Jain, Sanmati K.; Lanjhiyana, Sanjay K.; Ahirwar, Bharti; Gupta, Ajay; Jagan, B. G. V. S.; Vourdoubas, Ioannis S. (Challenges and Advances in Pharmaceutical Research Vol. 1, 2022)
Transport of drugs by oral route to colon becomes important in the treatment of colonic diseases like inflammatory bowel disease, ulcerative colitis, Chron’s disease, chronic pancreatic and colonic carcinomas. Metabolic reactions like hydrolysis, redox, deamination etc. and several biological features affecting oral drug delivery include the time spent in gastrointestinal tract (GIT), GI environment, microbial flora and enzymatic degradation and cumulatively all of which are obstructing drug delivery. Prodrug approach is one of the invaluable techniques for transportation of drugs by oral route to colon. In the present work azo prodrugs of 5-Amino Salicylic Acid (5-ASA), 4-ASA, anticancer drugs and newer leads useful in colonic diseases has been reviewed for the colon directed drug transport due to the selective cleavage of the azo bond by azoreductases discharged by the gut microflora.